Making sense of dying and death - Fagan, Andrew, 1966- (At the interface/probing the boundaries, 2004)
This book aims to extend upon the growing body of literature concerned with dying and death. The book analyses various experiences and representations of dying and death from the perspective of academic disciplines as diverse as theology, philosophy, sociology, anthropology, and literature. The rationale for this is simple. As objects of study dying and death cannot be usefully reduced to a single academic perspective. One cannot hope to gain a deep and comprehensive understanding of dying and death by gazing at them through a single lens. Bringing various perspectives in a single volume aims to both accurately record those enduring properties of the phenomena, such as mourning and fear, whilst simultaneously analysing the diversity and heterogeneity of human beings' attempts to come to terms with this most forbidding of existential horizons.